Vaginal foreign body in a 6 year old girl: a game for the child but a challenge for the gynaecologist - Chaurasia, Amrita; Gupta, Veena; Mishra, Akanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 6 year old girl visited our gynaecology out-patient department of S.R.N hospital, Allahabad, India with the complaint of relapsing blood stained vaginal discharge for 3 months. Different gynaecologists, including us, tried treating the condition with different courses of antibiotics. To each, the girl responded only for few days and relapsed again. We investigated completely into the background of the child’s home and school environment, her playing habits and her behaviour with her kins. Then, we got her various investigations done but with no derangement. With the backup of her history, examination and investigations, we performed another detailed examination of her genitals. The findings were intriguing as to their cause, and it definitely was a lesson to all of us.